2013
DOI: 10.1080/10889868.2012.751961
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of Heavy Metals (Cd2+, Cu2+, Co2+, and Mn2+) by Thermophilic Bacteria,Geobacillus thermantarcticusandAnoxybacillus amylolyticus: Equilibrium and Kinetic Studies

Abstract: Two strains of thermophilic bacteria, Geobacillus thermantarcticus and Anoxybacillus amylolyticus, were employed to investigate the biosorption of heavy metals including Cd 2+ , Cu 2+ , Co 2+ , and Mn 2+ ions. The effects of different biosorption parameters such as pH (2.0-10.0), initial metal concentrations (10.0-300.0 mg L −1 ), amount of biomass (0.25-10 g L −1 ), temperature (30-80 • C), and contact time (15-120 min) were investigated. Concentrations of metal ions were determined by using an inductively co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…The use of thermophilic bacteria in heavy metal remediation of polluted sites, or for metal removal from industrial waste, has been recently explored by different authors [17,18,19,20,35]. The use of thermophilic bacteria as passive heavy metal accumulators depends on their heavy metal resistance, the degree of contamination and the physical and chemical characteristics of the matrix to be remediated or de-polluted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of thermophilic bacteria in heavy metal remediation of polluted sites, or for metal removal from industrial waste, has been recently explored by different authors [17,18,19,20,35]. The use of thermophilic bacteria as passive heavy metal accumulators depends on their heavy metal resistance, the degree of contamination and the physical and chemical characteristics of the matrix to be remediated or de-polluted.…”
Section: Discussionmentioning
confidence: 99%
“…This could be a newly-found detoxification mechanism of thermophilic bacteria, as the previously described ones were passive mechanisms of heavy metals absorption on the bacterial cell surface [17,18,19,20], or through a specific soluble, cytoplasmic metal-binding protein able to increase the cellular efflux of heavy metals [22]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4) was found to be a fit better than the Langmuir (R 2 = 0.8963) and Temkin (R 2 = 0.9462) isotherm models. Various studies have reported the Freundlich [36,37] or Langmuir [38,39] or Temkin [40] isotherm models as the better fit in order to explain the biosorption behavior of different microorganisms.…”
Section: Isotherm Modelingmentioning
confidence: 99%
“…The amount of biosorbents is also a critical parameter that affects the biosorption performance. Various concentrations of biosorbents can vary the quantity of the biosorbed metal ions on biosorbents as well as the recovery capacity 23 . The impact of the biosorbent concentration was examined in the variety of 100-300 mg.…”
Section: Effects Of Amounts Of Biosorbent and Resinmentioning
confidence: 99%